(untitled) - Karina A. Rodrigues; Gustavo J. Macchi; Agueda Massa; María I. Militelli (Neotropical Ichthyology, 2013)
Percophis brasiliensis is a demersal species that constitutes an important resource of Argentine coastal fisheries. Nevertheless, information about bioenergetic dynamic of reproduction has not been reported. Therefore, seasonal variations of condition factors, biochemical composition and energy density of different tissues were analyzed in order to determine the strategy of energy allocation during the reproductive cycle of this species. Condition indices (hepatosomatic and K) showed a seasonal pattern opposite to that observed for gonadosomatic index, which was characterized by higher values during the reproductive period (spring-summer), decreasing at the end of spawning. Biochemical composition of different tissues also showed a clearly seasonality associated to reproductive cycle. Analysis of energy density variation of liver indicates that P. brasiliensis accumulate reserves in winter before reproduction, which later decrease during the spawning season. In contrast, the energy density in muscle did not show significant differences among seasons, indicating that individuals could be also using an external source of energy during spawning. Therefore, it is possible that P. brasiliensis respond to an intermediate strategy of energy allocation, combining characteristics of both capital breeders (stores energy previous to the onset of reproductive activity) and income breeders (acquire energy by active feeding during spawning period). Percophis brasiliensis é uma espécie demersal que constitui um recurso importante para a pesca costeira na Argentina. Não obstante, a informação sobre a dinâmica bioenergética da reprodução não tem sido reportada. Assim, as variações sazonais dos fatores de condição, composição bioquímica e densidade de energia de diferentes tecidos foram analisados para determinar a estratégia de alocação de energia durante o ciclo reprodutivo da espécie. Os índices de condição (hepatossomático e K) mostraram um padrão sazonal oposto ao observado para o índice gonadossomático, o qual foi caracterizado por valores mais elevados durante o período reprodutivo (primavera-verão), diminuindo no final da desova. A composição bioquímica de diferentes tecidos também mostrou uma sazonalidade claramente associada ao ciclo reprodutivo. Análise da densidade de energia do fígado indica que P. brasiliensis acumula energia no inverno, antes da reprodução, que mais tarde decresce durante a época de desova. Em contraste, a densidade de energia no músculo não mostrou diferenças significativas entre as estações do ano, indicando que os indivíduos poderiam ter também uma fonte externa de energia durante a reprodução. Portanto, é possível que P. brasiliensis responda a uma combinação das estratégias "capital breeder" (armazenam a energia antes do início da atividade reprodutiva) e "income breeder" (adquirem energia através da alimentação ativa durante o período de desova).